Penilaian Performa Keuangan PT. Kalbe Farma Tbk. dengan Metode Du Pont System - Reni Rianti Prastiti; Hari Sulistiyo (Penerbit Goodwood, 2022)
Purpose: This study aims to determine how effective PT. Kalbe Farma Tbk manages its financial ratio components. The research focuses on profitability ratios and activity ratios which are part of financial statement analysis using the Du Pont system method on the annual financial statements of PT. Kalbe Farma Tbk. Research methodology: The research was conducted using the databasee of the annual financial statements of PT. Kalbe Farma Tbk in the period 2016 - 2020 with the Du Pont system analysis method. The research method uses quantitative research with descriptive analysis and the data is processed using Microsoft Excel software. Result: The results of this study stated that the financial performance of PT. Kalbe Farma Tbk is still not effective even though the components in its financial statements are always increasing. The company's TATO continues to decline with an average of 1.16 rounds. NPM, ROE, and ROI are still in the process of increasing with an average of 12%, 17%, and 14%, respectively. EM whose condition is not stable with an average of 121%. Limitation: The limitations of this study are that it only uses five-year company financial data, there is no comparison with other companies in the same sector, and only focuses on variables from the Du Pont system analysis method. Contribution:This research is expected to be useful for the purposes of education, further research, and also the wider community.